Fabrication of carbon nanotube field effect transistors by transferring carbon nanotubes from growth substrate to device substrate - Mathews, Martin Paul. (2013)
Single wall carbon nanotubes (SWNTs) are grown on quartz or silicon substrates using chemical vapor deposition technique. Electron beam evaporation forms a thin layer of gold (100nm) on the SWNTs on the growth substrates (quartz or silicon). The SWNTs and gold layer can be transferred to device substrates (silicon wafer coated with SiO2) by using a carrier, such as polydimethyl siloxane (PDMS) or thermal tape. After transferring, the carrier is removed and the gold layer is eliminated by wet etching. The exposed SWNTs on the device substrates are used as the channel of CNTFETs. Source and drain of CNTFETs are fabricated using UV lithography and lift-off technique. Silicon wafer and SiO2 are used as back-gate and gate dielectric layer, respectively, for the CNTFETs. . Based on the CVD-grown SWNTs networks, SWNTs thin-film-transistors (TFTs) driving array for organic light-emitting diodes (OLED) displays was fabricated and characterized. The Id-VG, Id-VDS behaviors of the SWNTs TFTs were analyzed.